Exploring sexual knowledge and risk in the assessment and treatment of adolescent males with intellectual developmental disorders who display harmful sexual behaviour - Richards, Samantha (2018)
The aim of the current thesis was to explore sexual knowledge and risk in the assessment and treatment of adolescent males with intellectual developmental disorders (IDD), who display harmful sexual behaviour (HSB). A variety of methods were used in this undertaking, including a systematic review, a single case study, a critique of a psychometric measure and two empirical studies. The findings of the systematic review indicated that although the identified/assessed risk variables related to recidivism were found to be similar in cases and controls, some were found to be more prevalent for sexual offenders with IDD. However, it was difficult to draw any firm conclusions due to inconsistencies in findings and limitations in the methodological quality of included studies.